The Role of the Advisory Body for the Development and Preservation of Marriage (BP 4) in Reducing the High Divorce Rate in Cirebon District - Marifa Hasyanah; Nabilah Destini Sukmawati; Andieni Maudi Lestari; Moh Sigit Gunawan; Agus Dimyati (Interdiciplinary Journal and Hummanity (INJURITY), 2024)
The Advisory Board for Marriage Development and Preservation (BP4) is a community institution that seeks to reduce the divorce rate and improve the quality of marriage through various programs and activities aimed at maintaining and strengthening marriage bonds. This study aims to discuss the role of BP4 in implementing Article 1 of Law No. 1 of 1974 on the high divorce rate in Indonesia and the obstacles faced by BP4. The research method used in this study is an analytical descriptive approach with a normative juridical approach. The research contributes by analyzing the role and the challenges faced by this institution in enforcing this law, providing insights into the effectiveness of current efforts and suggesting potential improvements to better manage and reduce divorce rates.